Respuesta :

Answer:

[tex]x=-11[/tex]

Step-by-step explanation:

[tex]6x-2=7x+9[/tex]

Add 2 to both sides:

[tex]6x-2+2=7x+9+2[/tex]

[tex]6x=7x+11[/tex]

Subtract 7x from both sides:

[tex]6x-7x=7x+11-7x[/tex]

[tex]-x=11[/tex]

Divide both sides by -1:

[tex]\frac{-x}{-1}=\frac{11}{-1}[/tex]

[tex]x=-11[/tex]

Answer:

X= -11

Step-by-step explanation:

Simplifying

6x + -2 = 7x + 9

Reorder the terms:

-2 + 6x = 7x + 9

Reorder the terms:

-2 + 6x = 9 + 7x

Solving

-2 + 6x = 9 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.

-2 + 6x + -7x = 9 + 7x + -7x

Combine like terms: 6x + -7x = -1x

-2 + -1x = 9 + 7x + -7x

Combine like terms: 7x + -7x = 0

-2 + -1x = 9 + 0

-2 + -1x = 9

Add '2' to each side of the equation.

-2 + 2 + -1x = 9 + 2

Combine like terms: -2 + 2 = 0

0 + -1x = 9 + 2

-1x = 9 + 2

Combine like terms: 9 + 2 = 11

-1x = 11

Divide each side by '-1'.

x = -11

Simplifying

x = -11